The impact of crime on farms: an international synthesis - Donnermeyer, Joseph F. (Acta criminologica, 2018)
Crimes against agricultural operations around the world are both frequent and costly - financially, emotionally and socially. Yet, despite rural criminology’s emergence in the 21st century, the study of farm crime remains a relatively neglected area of inquiry. In part, this is due to the scattered nature of the literature. Journal articles and other publications about farm crime can be found in both criminological journals and a wide range of non-criminological sources, from scientific periodicals devoted to development, pastoralism and nomadic peoples, to publication outlets of agricultural colleges within the universities where scholars who have written about farm crime work. This article provides a synthesis of the literature, organised by four regions of the world where most of the known farm crime literature originates. The goal of this article is to provide a new generation of scholars with a single place where a large share of past research is discussed, and to build upon that base of knowledge to advance a future understanding of farm crime that informs alike academics, law enforcement and other criminal justice practitioners.